Hubungan Pengetahuan Bidan dengan Kepatuhan Penggunaan Alat Pelindung Diri dalam Pertolongan Persalinan di Puskesmas - Simamora, Siti Fatimah; Yuka, Aprillia Ayu Shinta; Wahyuni, Sari (Poltekkes Kemenkes Palembang, 2024)
Background: Clean and safe childbirth is far from expectations because practices for preventing infection are not in place due to the unavailability of delivery care standards, limited knowledge and skills required and lack of staff compliance with standards which causes the performance and quality of services to still be considered low. Knowledge about PPE and its benefits is very important for health workers to prevent the transmission of infections in health services and infection prevention efforts are the first step in providing quality health services.Objective: To determine the relationship between midwives' knowledge and compliance with the use of personal protective equipment (PPE) in childbirth assistance in the Muara Beliti Community Health Center work area in 2024.Method: This research is a quantitative research with a cross sectional approach. This research was conducted in the working area of the Muara Beliti Community Health Center in April 2024. The population in this study was all 42 midwives in the working area of the Muara Beliti Community Health Center. The sample in this study used a total sampling technique. The statistical test used is Chi Square analysis, with a significance level of á = 0.05.Results: The results of the univariate analysis showed that the majority of respondents (59.5%) adhered to the use of PPE in childbirth assistance and (71.4%) had good knowledge. The results of the bivariate analysis used the chi square test with a p value of 0.000 < α 0.05, meaning There is a relationship between midwives' knowledge of compliance with the use of PPE in childbirth assistance.Conclusion: there is a relationship between midwives' knowledge of compliance with the use of PPE in childbirth assistance in the Muara Beliti Community Health Center working area in 2024.